The potential of Dendrophthoe pentandra (L.) Miq and Scurrula ferruginea stem from Syzygium aqueum as source of natural antioxidant (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Many studies show the antioxidant ability of the parasite plant. This study aims to determine the capacity of Dendrophthoe pentandra (L.) Miq and Scurrula ferruginea stem from Syzygium aqueum to use as a natural antioxidant source. The sample was taken from the host Syzygium aqueum. The sampels were exraction with ethanol using maceration. The parameters determined spectrophotometrically using specific reagents that were antioxidant capacity using 1,1-diphenyl-2-picrylhydrazyl, phenolics compounds using Folin-Ciocalteu, flavonoids using AlCl3, ascorbic acid using sulfosalicylic acid, while chlorophyll and carotenoid using dimethyl sulfoxide. The result of D. pentandra (L.) Miq and S. ferruginea extract showed that IC50 were 15.09±1.02 and 20.53±1.77 mg/ml, content of phenolics compounds were 557.45±19.77 and 433.99±20.89 mg GAE/ml extract, flavonoids were 9.72±0.23 and 3.02±0.71 mg QE/ml extract, chlorophylls-a were 2.67± 0.15 and 2.77±0,08 mg/g extract, chlorophylls-b were 3.34±0.06 and 3.44±0.04 mg/g extract, total chlorophylls were 6.01±0.21 mg/g extract, carotenoids were 1.71±0.01 and 2.10±0.01 mg/g extract respectively. The stems of both D. pentandra (L.) Miq and S. ferruginea from Syzygium aqueum have very strong antioxidant abilities so that they are potential to use as a source of natural antioxidants. The compounds support the antioxidant activity were phenolic, flavonoids, and ascorbic acids. The results of this study will open up opportunities to obtain new sources of antioxidants that can be utilized in human health management.